GPIb is involved in platelet aggregation induced by mucetin, a snake C-type lectin protein from Chinese habu (Trimeresurus mucrosquamatus) venom - Lu, Qiumin; Navdaev, Alexei; Clemetson, Jeannine M.; Clemetson, Kenneth J. (Thrombosis and Haemostasis, 2004)
Mucetin (Trimeresurus mucrosquamatus venom activator, TMVA) is a potent platelet activator purified from Chinese habu (Trimeresurus mucrosquamatus) venom. It belongs to the snake venom heterodimeric C-type lectin family and exists in several multimeric forms. We now show that binding to platelet glycoprotein (GP) Ib is involved in mucetin-induced platelet aggregation. Antibodies against GPIb as well as the GPIb-blocking C-type lectin echicetin inhibited mucetin-induced platelet aggregation. Binding of GPIb was confirmed by affinity chromatography and Western blotting. Antibodies against GPVI inhibited convulxin- but not mucetin-induced aggregation. Signalling by mucetin involved rapid tyrosine phosphorylation of a number of proteins including Syk, Src, LAT and PLCγ2. Mucetininduced phosphorylation of the Fcγ chain of platelet was greatly promoted by inhibition of αIIbβ3 by the peptidomimetic EMD 132338, suggesting that phosphatases downstream of αIIbβ3 activation are involved in dephosphorylation of Fcγ. Unlike other multimeric snake C-type lectins that act via GPIb and only agglutinate platelets, mucetin activates αIIbβ3. Inhibition of αIIbβ3 strongly reduced the aggregation response to mucetin, indicating that activation of αIIbβ3 and binding of fibrinogen are involved in mucetin-induced platelet aggregation. Apyrase and aspirin also inhibit platelet aggregation induced by mucetin, suggesting that ADP and thromboxane A2 are involved in autocrine feedback. Sequence and structural comparison with closely related members of this protein family point to features that may be responsible for the functional differences.
Keywords: Snake venom; C-type lectin; platelets; GPIb; tyrosine phosphorylation